Re-contextualisation in in-company vocational education in the dual system in Germany - Höhns, Gabriela [Verfasser] (My University, 2016)
This chapter "shows the adaptability of Bernstein's concept 'recontextualisation' to new empirical contexts. The German dual system of vocational education is presented as a case where the creators of a discourse are also its recontextualisers, a case never before systematically analysed with Bernsteinian concepts. The chapter adds to Bernstein's concepts the empirical finding of legitimate boundaries to a primary discourse. It shows that a differently produced pedagogic discourse takes effect in a different relationship of time, space and discourse and in different subject projections, while Bernstein's basic assumptions about the pedagogic device still hold." The research is based on a documentary analysis of central legislative texts, especially the Vocational Training Act (Berufsbildungsgesetz - BBiG) and the Trade and Crafts Code (Handwerksordnung - HwO). (Authors' abstract, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; T 2.1 Bildungstheorien; Betriebliche Berufsausbildung; Beruflichkeit; Bildungstheorie